Update and Outlook for 2005 of Florida's BMP Program for Vegetable Crops - Celeste A. Gilbert; Eric H. Simonne (EDIS)
With the onset of the implementation of the BMP program for vegetable crops, growers may be interested, concerned and confused about how the program will affect their production practices. This publication is meant to answer some of these concerns and provide an update on the status of the BMP manual for vegetable crops, with an emphasis on the rule making progress and acceptable strategies for nutrient management. This document is HS1013, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2005.